Gesturers Tell a Story Creatively; Non-Gesturers Tell it like it Happened. Issue 3 (2nd July 2020) - Laurent, Angélique; Smithson, Lisa; Nicoladis, Elena
ABSTRACT: Previous research has shown that using gestures helps children remember more information. Here, we designed two studies to test whether children who gesture tend to rely on visuospatial cognitive resources more than children who do not gesture. We also test whether children who gesture demonstrate more creativity in their narrative productions. Preschool children watched a cartoon and then were asked to tell back the story of the cartoon. In the first study, some children were asked to tell the story with gestures constrained while others could move their hands if they chose. Children who did not spontaneously gesture told shorter stories than children who gestured. The sequencing of story events was significantly closer to the original among the Non-Gesturers than among children whose gestures were constrained. In the follow-up study, Non-Gesturers again told shorter stories than Gesturers. Moreover, Non-Gesturers' story length was positively correlated with both verbal and visuospatial short-term memory. Overall, these results suggest that, when retelling narratives, preschoolers who gesture may be relying upon visuospatial cognitive resources to a greater extent and show a tendency to incorporate more creativity into their narratives compared to preschoolers who did not spontaneously gesture.